PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADAPERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI): PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADAPERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Mira Diyanty; Meina Wulansari Yusniar (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
The purpose of this study was to analyze the effect of the Good Corporate Governance mechanism on the board of commissioners, the board of directors, the proportion of independent commissioners, the audit committee, CAR on ROA. This study also uses a purposive sampling method for sampling. The analysis test used is multiple linear regression analysis. The population used by companies listed on the Indonesia Stock Exchange in the period 2011 - 2013 and which meet the sample selection criteria. The sample used was 25 companies. Data is collected through secondary data collection in the form of the company's annual report for the period 2011 - 2013 which is published on the Indonesia Stock Exchange. The research hypothesis was tested by multiple linear regression which had met the testing of classical assumptions. The results of the analysis show that the board of commissioners, the proportion of independent commissioners, audit committees, CAR does not significantly influence ROA while the board of directors has a positive and significant effect on ROA.